2022
DOI: 10.3390/ijerph19052713
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Seminal Oxidative Stress Scavenging System in the Pathogenesis of Sperm DNA Damage in Men Exposed and Not Exposed to Genital Heat Stress

Abstract: Responding to the need for the verification of some experimental animal studies showing the involvement of oxidative stress in germ cell damage in the heat-induced testis, we investigated the possibility of a direct relationship between seminal oxidative stress markers (total antioxidant capacity, catalase activity, superoxide dismutase activity, and malondialdehyde concentration) and ejaculated sperm chromatin/DNA integrity (DNA fragmentation and chromatin condensation abnormalities) in distinct groups of men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Furthermore, we can assume that in the semen of infertile men without leukocytospermia, total antioxidant capacity (TAC), antioxidant enzymes, and molecule activity are decreased. An association between male infertility, the level of TAC, and the activity of antioxidant enzymes and molecules (catalase, superoxide dismutase, glutathione) was confirmed [ 10 , 46 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we can assume that in the semen of infertile men without leukocytospermia, total antioxidant capacity (TAC), antioxidant enzymes, and molecule activity are decreased. An association between male infertility, the level of TAC, and the activity of antioxidant enzymes and molecules (catalase, superoxide dismutase, glutathione) was confirmed [ 10 , 46 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, wet testis hyperthermia has a reversible negative effect on sperm motility ( Shefi et al, 2007 ). In a very recent study, Fraczek et al evaluated sperm parameters, sperm DNA integrity, and major markers of oxidative stress, in subjects who voluntarily underwent a semen test and completed a lifestyle questionnaire ( Fraczek et al, 2022 ). Compared to controls, study participants reporting prolonged genital heat stress, namely, professional drivers and infertile men with varicocele, showed that the total sperm antioxidant capacity was reduced ( Fraczek et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to controls, study participants reporting prolonged genital heat stress, namely, professional drivers and infertile men with varicocele, showed that the total sperm antioxidant capacity was reduced ( Fraczek et al, 2022 ). On the other hand, the catalase activity and sperm DNA fragmentation both increased ( Fraczek et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is the main reason of sperm DNA fragmentation, which is caused by endogenous and exogenous factors. Although sperm function requires proper reduction and oxidative balance, antioxidants play a protective role in reducing oxidative stress [1][2][3]. Researchers have found that reactive oxygen species (ROS), especially superoxide anion, hydroxyl radicals and hydrogen peroxide, are normal by-products in various metabolic and physiological processes, but excessive production can lead to oxidative stress [4,5].…”
Section: Introductionmentioning
confidence: 99%